Living Hadith: Concept, Role, and Development in Indonesia - Saputra, Edriagus; Nana Gustianda; Wendry, Novizal; Arwansyah bin Kirin; Zakiyah, Zakiyah; Afrinaldi, Afrinaldi; Syahidin, Amal; Putra, Alven (Islam Transformatif : Journal of Islamic Studies, 2024)
This study aims to explore the development and role of living Hadith in Indonesia. Using qualitative methods and a library research approach, this study highlights living Hadith research through the Dimensions website. The findings reveal that living Hadith plays a crucial role in bridging Islamic teachings with local culture, strengthening regional religious identities, and fostering harmony between religion and local wisdom. Additionally, this approach addresses the limitations of rigid and textual traditional normative methods by exploring the actualization of Hadith in social practices and traditions. Living Hadith research contributes to critically evaluating, improving, and reforming traditions to align with Islamic teachings while promoting religious moderation through tolerant, inclusive, and adaptive understandings of Indonesia's cultural diversity. Searches through Dimensions identified 220 scholarly articles on living Hadith, while VOSviewer analysis found 100 researchers contributing to this field. This study affirms that living Hadith development in Indonesia has significantly advanced since the early 2000s, driven by contributions from academics at UIN, IAIN, and STAIN. It highlights the importance of living Hadith in ensuring the relevance of Islam to contemporary changes while preserving the values of togetherness in a pluralistic society.